The Cemetery in Opinogóra. Traces of human resumes - Górczyk, Wojciech Jerzy (In the Mirror of Things, 2022)
Funeral rites are one of the cultural attributes of death. They may have private, almost intimate character or involve a public ceremonial. The cemetery combines both of them: it is a public and a private place at the same time. As a publicly accessible space, cemetery is also a place where we can visit the graves of our close family and friends in complete privacy and in the atmosphere of silent contemplation. Graves are a material trace of the dead. They help us keep the memory of those who passed away. No wonder, some of the sepulchral decorations are works of art. This is also true for the cemetery in Opinogóra, which was established in the 1820s. The tomb sculptures were created by renowned artists like Józef Czerwiński (student of the outstanding sculptor Pawel Maliński). The historic tombs are stark and modest in character, and nowadays they are admired just for this simplicity. Even the ones which are most interesting in form are not sumptuous and draw on apparently simple imagery. The memorial park in Opinogóra is also famous for the crypts of the Krasiński counts, heirs of the Opinogóra estate. Among the most notable ones are: the marble sepulchral statue of countess Maria Urszula Krasińska née Radziwiłł, sculpted by the Italian artist Luigi Pampaloni in 1841, the marble epitaph to Zygmunt Kraisiński’s sons, executed in 1875 by the Italian artist Jules Franceschini, and the epitaph to countess Amelia Załuska née Bronikowska, created by Konstanty Laszczka in 1899.